Successful treatment of a classic Hodgkin lymphoma‐type post‐transplant lymphoproliferative disorder with tailored chemotherapy and Epstein–Barr virus‐specific cytotoxic T lymphocytes in a pediatric heart transplant recipient. (1st September 2013) - Basso, Sabrina; Zecca, Marco; Calafiore, Lucia; Rubert, Laura; Fiocchi, Roberto; Paulli, Marco; Quartuccio, Giuseppe; Guido, Ilaria; Sebastiani, Roberta; Croci, Giorgio Alberto; Beschi, Claudia; Nardiello, Ida; et al.
Abstract CHL type is the least common major form of EBV‐related PTLD but rarely occurs in pediatric recipients; development of CHL subsequent to other PTLD subtypes in the same transplant recipient is even more unusual. Because of its rarity, indications on the best treatment strategy are limited. Patients have been mostly treated with standard HL chemotherapy/radiotherapy, and prognosis seems more favorable than other monomorphic PTLDs. Herein, we describe a pediatric case of EBV‐associated, stage IV‐B, CHL arising in a heart allograft recipient eight yr after diagnosis of B‐cell polymorphic PTLD. The patient was successfully treated with adjusted‐dose HL chemotherapy and autologous EBV‐specific CTL, without discontinuation of maintenance immunosuppression. At two yr from therapy completion, the patient is in CR with stable organ function. With this strategy, it may be possible to reproduce the good prognostic data reported for CHL‐type PTLD, with decreased risk of organ toxicity or rejection.